The effect of abusive supervision on employee silence with the mediation role of emotional exhaustion and moderate leader-member exchange - Sridadi, Ahmad Rizki; Admojo, Rifki Tri Cahyo; Himmawan, Muhammad Fikri; Fuciu, Mircea (Universitas Negeri Surabaya, Indonesia, 2022)
Employee silence is a phenomenon in the workplace where an employee withholds all ideas and information, triggered by emotional exhaustion resulting from negative affectivity, such as abusive supervision in the workplace. The leader-member exchange level also affects employees' intensity when holding back all ideas and information they have at work. This study aims to determine the effect of abusive supervision on employee silence, mediated by emotional exhaustion and the moderating effect of leader-member exchange. The variables used in this study are abusive supervision, employee silence, emotional exhaustion, and leader-member exchange. This study used quantitative methods and questionnaires as data collection tools and analysed it using PLS. One hundred PT. XYZ’s employees participated in this study as the respondent. This study shows that abusive supervision significantly affects employee silence and emotional exhaustion. Emotional exhaustion partially mediates the impact of abusive supervision on employee silence, and leader-member exchange does not moderate the effect of abusive supervision on emotional exhaustion. The novelty of study leverages employee emotional exhaustion instead of organizational politics to mediate the relationship between abusive supervision and employee silence.